Pengaruh Kualitas Produk, Harga, Dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Angkringan Van Java Desa Banyuurip Ujungpangkah Kabupaten Gresik - Al Muktafa, Lam Ush Shofie; Basalamah, Muhammad Ridwan; Wahono, Budi (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to determine the effect of product quality, price, and service quality on customer satisfaction at Angkringan Van Java located in Banyuurip Village, Ujungpangkah District, Gresik Regency. The results of the study indicate that simultaneously, product quality, price, and service quality have a significant effect on customer satisfaction. This means that customer satisfaction is influenced by a combination of these three factors. Therefore, to improve customer satisfaction, companies need to pay attention to and improve these three elements simultaneously.However, when analyzed partially, product quality was found to have a significant negative effect on customer satisfaction. competitive and in line with customer expectations will be very important to maintain high customer satisfaction.In addition, service quality also has a positive and significant effect on customer satisfaction. This shows that the service provided by Angkringan Van Java staff is considered good by customers. Friendly, fast, and responsive service to customer requests are key factors in creating a positive experience for customers. Good service quality can strengthen the relationship between customers and the company, as well as increase customer loyalty, which is very important in the food and beverage service industry. Keywords: Product Quality, Price, Service Quality